PROBLEMS IN THE APPLICATION OF GOOGLE TRANSLATE AS A LEARNING MEDIA IN TRANSLATION - Christanta Rejuna Phanes Sembiring Brahmana; Rudy Sofyan; Dian Marisha Putri (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This paper is concerned with the problems in the application of Google Translate as a translation tool. The discussion focuses on the identification of the problems faced by the translators. This research was conducted by using the descriptive qualitative method with a case study approach. Some theories supporting this research were proposed by Munday, Imre, and also Ghasemi and Hasemian. The data sources in this research were taken from the questionnaires given to students of English Literature Department of USU. From the analysis, it was found that the biggest problems often faced by the students of English Literature Department of USU were the inaccuracy and mismatch of the meaning translated which reached 31%, followed by the inaccuracy of the language structure in the translation result which reached 30%. On the other hand, the findings also showed that the best solution to deal with these problems was to make self-corrections and check the meaning of some suspected words in the dictionary and make the best choice according to the context. With the same percentage of 29%, it could be concluded that the two solutions were claimed to be the best and most efficient for the students. The conclusion was that the use of Google Translate as a learning media in translation could be accepted and applied in the classroom. Based on the results of this analysis, it was revealed that students had already known how to solve the problems of using Google Translate.